Base nacional comum curricular e o "novo" ensino médio: análise a partir dos pressupostos teóricos da pedagogia histórico-crítica - Zank, Debora Cristine Trindade (2020)
This work discusses the implementation of the National Common Curricular Base - BNCC (Brazil, 2018) and the “New” High School, effective from 2016. Therefore, we reflect on the foundations used to articulate this curriculum, and the main objectives and the possible consequences for youth, especially those who attend public school, who are sons and daughters of the working class. We take as a basis the dialectical and materialistic perspective of Historical-Critical Pedagogy describing the concepts of man, education, educational work, objective knowledge, curriculum and polytechnic as theoretical bases for the analyzes in this research. We investigated some changes that occurred in the history of high school and the relationship with the training of workers, as a basis to understand and relate the changes made today, especially with regard to the vote on the pedagogy of skills, already used in the late 1990s. To understand this articulation, the official documents released by the federal government were analyzed, as well as the scientific production related to the theme of reform and BNCC presented in books, articles and thesis banks of universities. With these analyzes we have the hypothesis that the training given to youth from the current reform is a training of skills and emptying of contents and is far from the intention of a emancipatory training of individuals. Starting from the theoretical bases presented to support the analyzes, we discuss the definition of Historical-Critical Pedagogy on secondary education, reflecting on the need for a curricular organization that goes in the opposite direction to the training of skills and the emptying of content and adequate therefore, to the formation of youth as a formation against hegemony, providing education with access to all the contents historically developed by humanity with the objective of training young people with conditions to understand the social organization and transform it.